Analysis of the Implementation of Human Resource Development at the Department of Trade and Industry in Gowa Regency, South Sulawesi Province - Emi Erti Nengsi (Pustaka Digital Indonesia, 2022)
This research aims to determine the implementation of human resource development at the Department of Trade and Industry in Gowa Regency. This type of research used in this research is descriptive research with a qualitative approach. Data collection techniques used in this study through observation (observation), interviews and documentation. The results showed that the Department of Trade and Industry in the implementation of human resource development carried out the Education and Training method of the DIKLAT program. The result can have quality employees with good abilities and skills.